Role of the Internet in Internet-enabled Born Global Key Success Factors - Saukkonen, Joonas (My University, 2014)
This thesis’ purpose is to study what is the Internet’s role in Internet-enabled born global key success factors through a single case study of a Finnish born global company Sportsetter. The born global phenomenon and the Internet have been studied thoroughly but there is little to no research of the Internet in born global companies. This thesis opens the research area left for little attention. The research’s theoretical framework is based on the identification of key success factors in born global companies and identification of what the Internet’s role in success has found out to be in small and medium-sized enterprises and its possible role in born global key success factors. The empiric analysis is based on the themes rising from theoretical framework. Empiric data has been gathered from the case company using semi-structured interview as data gathering method and the whole research is conducted with case study strategy. Research findings support earlier born global research on what are the key success factors for these kinds of companies. The Internet utilization in the case company supported the theories suggested for Internet-enabled companies rather than traditional Internet-adoption models. The Internet’s role in the case company’s key success factors was found out as information and knowledge provider and as an effective tool for marketing and branding. Also the Internet’s role in the case company’s marketing and branding was seen important.
Keywords: born global; key success factor; Internet; Internet-enabled; SME; fi=Markkinointi|en=Marketing|; fi=Markkinoinnin johtamisen maisteriohjelma|en=Master's Programme in Marketing Management|